THE PROBLEMS AND PERSPECTIVES OF TEACHING COMMUNICATIVE BEHAVIOR IN THE ENGLISH CLASSROOMS - Dilorom Ahmedova, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This paper delves into the complexities surrounding the instruction of communicative behavior within English classrooms. It examines the various challenges encountered by educators in fostering effective communication skills among students, such as cultural differences, language and behavioural  barriers. Furthermore, it explores the evolving perspectives on teaching communicative behavior, highlighting the importance of incorporating real-life contexts, interactive methodologies, and inclusive practices. By analyzing existing literature and pedagogical approaches, this article offers insights into potential solutions and future directions for enhancing intercultural competence in English language education.